"Constrained Medical Oxygen Supply Chain in India During COVID-19: Red-tapism, the Elephant in the Room?". (14th October 2023) - Gowda, Naveen R.; Siddharth, Vijaydeep; Kumar, Parmeshwar; Vikas, H.; Swaminathan, Prakash; Kumar, Atul
Abstract: Background: Recent disruption of medical oxygen during the second wave of coronavirus disease 2019 (COVID-19) has caused nationwide panic. This study attempts to objectively analyze the medical oxygen supply chain in India along the principles of value stream mapping (VSM), identify bottlenecks, and recommend systemic improvements. Methods: Process mapping of the medical oxygen supply chain in India was done. Different licenses and approvals, their conditions, compliances, renewals, among others were factored in. All relevant circulars (Government Notices), official orders, amendments, and gazette notifications pertaining to medical oxygen from April 2020 to April 2021 were studied and corroborated with information from Petroleum and Explosives Safety Organization (PESO) official website. Results: Steps of medical oxygen supply chain right from oxygen manufacture to filling, storage, and transport up to the end users; have regulatory bottlenecks. Consequently, flow of materials is sluggish and very poor information flow has aggravated the inherent inefficiencies of the system. Government of India has been loosening regulatory norms at every stage to alleviate the crisis. Conclusions: Regulatory bottlenecks have indirectly fueled the informal sector over the years, which is not under Government's control with difficulty in controlling black-marketing and hoarding. Technology enabled, data-driven regulatory processes with minimum discretionary human interface can make the system more resilient.